Imaging Unique DNA Sequences in Individual Cells Using a CRISPR-Cas9-Based, Split Luciferase Biosensor - Heath, Nicholas G.; O’Geen, Henriette; Halmai, Nicole B.; Corn, Jacob E.; Segal, David J. (Frontiers in Genome Editing, 2022)
An extensive arsenal of biosensing tools has been developed based on the clustered regularly interspaced short palindromic repeat (CRISPR) platform, including those that detect specific DNA sequences both in vitro and in live cells. To date, DNA imaging approaches have traditionally used full fluorescent reporter-based fusion probes. Such “always-on” probes differentiate poorly between bound and unbound probe and are unable to sensitively detect unique copies of a target sequence in individual cells. Herein we describe a DNA biosensor that provides a sensitive readout for such low-copy DNA sequences through proximity-mediated reassembly of two independently optimized fragments of NanoLuc luciferase (NLuc), a small, bright luminescent reporter. Applying this “turn-on” probe in live cells, we demonstrate an application not easily achieved by fluorescent reporter-based probes, detection of individual endogenous genomic loci using standard epifluorescence microscopy. This approach could enable detection of gene edits during ex vivo editing procedures and should be a useful platform for many other live cell DNA biosensing applications.